Harnessing Real-World Projects A Strategic Proposal for Industry Engagement and Income Generation in Malaysia’s Technical Universities - Syafiq Fauzi, Kamarulzaman (UMPSA, 2023)
As the financial landscape of higher education evolves globally, innovative solutions are being sought. A forward-thinking approach involves the transformation of classrooms in Malaysia’s technical universities into project centres. In these centres, academic staff mentor students to develop real-world solutions for projects provided by industry clients. This model aligns with national policy goals and serves a dual purpose: acting as an income source and promoting experiential learning.